Experimental and computational investigation on underlying factors promoting high coke resistance in NiCo bimetallic catalysts during dry reforming of methane - Tinnakorn Saelee (Nature Portfolio, 2021)
Abstract Global warming remains one of the greatest challenges. One of the most prominent solutions is to close the carbon cycle by utilizing the greenhouse gas: CO2, and CH4, as a feedstock via the dry reforming of methane (DRM). This work provided an insight into how the NiCo bimetallic catalyst can perform with high stability against coking during DRM compared to the Ni and Co monometallic catalysts, in which the experimental and computational techniques based on density functional theory were performed. It was found that the high stability against coking found on the NiCo surface can be summarized into two key factors: (1) the role of Co weakening the bond between a Ni active site and coke (2) significantly high surface coke diffusion rate on NiCo. Moreover, the calculation of the surface fraction weighted rate of coke diffusion which modeled the real NiCo particle into four regions: Ni-dominant, Co-dominant, NiCo-dominant, and the mixed region consisting a comparable amount of the former there regions, have shown that the synthesis of a NiCo particle should be dominated with NiCo region while keeping the Ni-dominant, and Co-dominant regions to be as low as possible to facilitate coke diffusion and removal. Thus, to effectively utilize the coke-resistant property of NiCo catalyst for DRM, one should together combine its high coke diffusion rate with coke removal mechanisms such as oxidation or hydrogenation, especially at the final diffusion site, to ensure that there will not be enough coke at the final site that will cause back-diffusion.